Gender disparity in Literacy in Bareilly district - Devi, Geeta; Tiwari, Seema (National Geographical Journal of India, 2022)
Literacy has been considered as one of the prime determinants of the socio-economic development. In this context, education has become an important gateway for upgrading the socio-economic status of the people of a region. From a geographical point of view, literacy rate varies from region to region and withthe passage of time, it assumes spatio-temporal characteristic. According to the census of India 2011, the overall rate of literacy of the country is 74% with the male literacy rate being 81% against 64.40% of female literacy. So, a large gap can be seen between male-female literacy rate. Despite number of efforts done at both state and national level, there remains a large number of illiterate people, existing in the society and presents major hurdle in the socio-economic development of the region. This scenario is a matter of great concern. An attempt has been made in this paper to map and analyze the gender gap in literacy rate of Bareilly district. This study is based upon secondary sources of data. This paper provides an insight into the existing spatio-temporal patterns of male-female literacy rate and its level of disparity. The findings suggest that a significant difference undoubtedly, exist between male and female literacy rate at block level in Bareilly district.